Immobilized Talaromyces thermophilus lipase as an efficient catalyst for the production of LML-type structured lipids - Lian, Weishuai (Springer, 2019)
LML-type structured lipids are one type of medium- and long-chain triacylglycerols. LML was synthesized using immobilized Talaromyces thermophilus lipase (TTL)-catalyzed interesterification of tricaprylin and ethyl linoleate. The resin AB-8 was chosen, and the lipase/support ratio was determined to be 60 mg/g. Subsequently, the immobilized TTL with strict sn-1,3 regiospecificity was applied to synthesize LML. Under the optimized conditions (60 °C, reaction time 6 h, enzyme loading of 6% of the total weight of substrates, substrate of molar ratio of ethyl linoleate to tricaprylin of 6:1), Triacylglycerols with two long- and one medium-chain FAs (DL-TAG) content as high as 52.86 mol% was obtained. Scale-up reaction further verified the industrial potential of the established process. The final product contained 85.24 mol% DL-TAG of which 97 mol% was LML after purification. The final product obtained with the high LML content would have substantial potential to be used as functional oils.